Effect of low temperature CO2 injection in high temperature oil reservoirs using slimtube experiment - Hamdi, Z. (Penerbit UTM Press, 2016)
A set of slimtube experiments is designed and presented to study the effect of cold temperature CO2 on recovery factor in reservoirs with high temperature. The comparison of the results indicates the positive effect of temperature on recovery trend in early stage as well as ultimate recovery in different injection pressures. The approach is based on a long slimtube to show the effect of temperature on the recovery. The study considers different temperatures and pressures of injection and reservoir allowing both miscible and immiscible flooding of CO2. Using non-isothermal conditions, the results show that, lowering temperature of injection can yield in higher recovery in early stage significantly. Also, considering ultimate recovery, it is observed that low temperature CO2 injection into high temperature reservoir can result in slightly higher recovery factor than isothermal injection. The reason for recovery increase is mainly due to elimination of the interfacial tension between CO2 and reservoir fluids especially near the injection point. Another finding is that the minimum miscibility pressures is lowered by means of lowering the temperature of injection which is again caused by elimination of interfacial tension between CO2 and oil. This is important because forming a single phase can increase the ability of CO2 to extract different components of the crude oil as well as lowering viscosity of the mixture, resulting in a better sweep efficiency. It appears that using liquid CO2 in high temperature reservoirs can be a promising method for better oil recovery in high temperature reservoirs. Â© 2016 Penerbit UTM Press. All rights reserved.